ANALYSIS OF OFFSHORE GAS PRODUCTION OPTIMIZATION BY REDUCING PIPELINE PRESSURE TOWARDS GAS PROCESSING FACILITY - ISKANDAR DINATA MUDA HASIBUAN - NIM: 23016020 , BINTO
The oil and gas industry depends on the wellhead production performance. On mature field, where the wells produced for long time, resulting in decreasing of reservoir volume as well as reservoir pressure. However, PT ABC has a binding agreement of gas sales with refinery of PT PR. The minimum gas supply in daily basis is 35 MMscfd, although in historical data shown minimum gas supply is 45 MMscfd. The source of gas is coming from offshore platform of X, Y and Z field located at Balikpapan and Penajam, East Kalimantan. In order to meet gas supply commitment then an effort is required to fulfill the supply. One of the production optimization method is a surface facility optimization by using gas compressor to reduce backpressure from the onshore processing facility to Y and Z offshore production platform resulting in lower wellhead pressure. Reutilization of inactive compressor is an efficient method to avoid capital cost for production optimization. Centrifugal compressors are used to deliver gas at volumetric rate with certain compression ratio refers to compressor performance curve. By reducing the pipeline system pressure from 350 Ã‚Â– 400 psig to 150 psig, then impact to production gain from both fields. Production incremental has a certain probability in accordance to the recommendations of reservoir engineering. Production forecast is a reference to analyze the optimization result. In thermodynamic, decreasing the wellhead pressure will affect to fluid phase change, then it is important to analyze the surface facilities capacity such as slug catcher and separator, affect on multiphase pipeline and piping system in accordance with industrial engineering standard to ensure production optimization is safe and reliable.